Discorso al Bundestag, Berlin, 22.09.2011 - Benedikt XVI. Papst 1927-2022 (2012)
Mit Anmerkung von del Pozzo, Massimo auf den Seiten 169-181
Keywords: Benedikt -- XVI. -- Papst -- 1927-2022; Papst; Rede; Deutschland